COVID-19 social and economic impacts: A comparative analysis in Southern European countries - updating for SWE - Belchior-Rocha, H.; Casquilho-Martins, I.; Capucha, Luís (European Conference of Social Work Education 2023, 2023)
The COVID-19 pandemic globally affected European societies. This new crisis arrived after a period of gradual recovery from the 2008 financial crisis that had jeopardized the achievement of Europe Strategy 2020 (ES2020) targets. The need to recover for the Southern European countries, which had austerity programs during the financial crisis, is crucial to ensure a continuum of economic and social development. This study aimed to analyze the impact of the two last international crises on the accomplishment of ES2020 goals and how the ‘NextGenerationEU’ program presents a mechanism to recover from the pandemic’s socioeconomic impacts. We analyzed secondary statistical data from Eurostat and official European documents. Additionally, we carried out a systematic analysis of 162 measures of the recovery and resilience plan from Southern European countries (Greece, Spain, Italy, and Portugal). The results showed that ES2020 targets were at risk, particularly in the field of employment, combating poverty, and social exclusion. Currently, there is strong European investment in response to the socioeconomic impacts of the pandemic, with all countries defining measures adjusted to protect the most vulnerable groups. However, the implications of these responses require a political commitment for them to effectively contribute to sustainable recovery and development. Therefore there is a need for Social Workers update their training and in the future the need to increase their professional skills.